2018
DOI: 10.1002/hipo.22992
|View full text |Cite
|
Sign up to set email alerts
|

A new human delayed‐matching‐to‐place test in a virtual environment reverse‐translated from the rodent watermaze paradigm: Characterization of performance measures and sex differences

Abstract: Watermaze tests of place learning and memory in rodents and corresponding reverse‐translated human paradigms in real or virtual environments are key tools to study hippocampal function. In common variants, the animal or human participant has to find a hidden goal that remains in the same place over many trials, allowing for incremental learning of the place with reference to distal cues surrounding the circular, featureless maze. Although the hippocampus is involved in incremental place learning, rodent studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(45 citation statements)
references
References 100 publications
(239 reference statements)
2
40
1
Order By: Relevance
“…However, when the goal location changes, the model needs many trials to adjust in order to accurately navigate to the new goal, which is in marked contrast with real DMP performance of rats ( Fig. 1b) and humans (Buckley and Bast 2018).…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…However, when the goal location changes, the model needs many trials to adjust in order to accurately navigate to the new goal, which is in marked contrast with real DMP performance of rats ( Fig. 1b) and humans (Buckley and Bast 2018).…”
Section: Discussionmentioning
confidence: 87%
“…Hence, the model can be considered as a model of one shot recall, rather than one-shot learning. This cannot account for the onetrial place learning performance shown by rats and human participants on DMP tasks towards new goal locations, rather than familiar ones (Bast et al 2009;Buckley and Bast 2018). However, the hierarchical RL model may account for onetrial place learning performance on the DMP task when the changing goal locations are familiar goal locations, i.e.…”
Section: Limitations In Accounting For Open Field Dmp Performancementioning
confidence: 97%
See 3 more Smart Citations